Ancaman Deepfake Buatan AI Dan Implikasinya Terhadap Keamanan Data Biometrik Di Indonesia - Palindria, Arvi Erawan; Thufail, Muhammad Sulthan; Febrian, Muhammad Rieval (PMIH Untag Semarang, 2024)
Throughout its evolution, artificial intelligence not only has positive impacts on mankind. One of which is Deepfake, an AI model that poses a serious threat to the security of biometric data, which is a type of specific personal data. Regulations regarding biometric data can be found in Undang-Undang Nomor 27 Tahun 2022 tentang Pelindungan Data Pribadi. However, these regulations do not specifically address biometric data. The existence of deepfake, which could manipulate videos and/or photos, becomes a serious threat that needs attention. Therefore, the objective of this research is to identify the threats posed by deepfake technology to biometric data security and the roles of the government and industry in anticipating these threats. This research was conducted using a normative juridical legal research method with a statute approach and a conceptual approach using futuristic interpretation. The findings from this research journal indicate that the absence of specific protection for biometric data security leads to the vulnerability of biometric data to misuse. The government's role is needed to establish Peraturan Pelaksana Undang-Undang Pelindungan Data Pribadi and regulation that specifically addresses biometric data